The influence of familiarization on performance testing of young soccer players - Cicero Xavier de Oliveira, Donizete; Rossi Gonçalves, Hélcio; Denardi, Renata; Oliveira, Vitor; Deminice, Rafael (Motriz : Revista de Educação Física. Unesp, 2024)
Abstract - Aim To investigate the effects of the familiarization trials to minimize the impact of intra-subject variation on the performance evaluation of soccer athletes. Methods: Twenty-five players from an under-19 soccer team were submitted to three performance tests: vertical jump test, test of change-of-direction (Agility T-test) and running anaerobic sprint test (RAST). The three performance tests were repeated on three subsequent days as familiarization sessions until the fourth/last session. Familiarization sessions were performed once a day under the same conditions. For the analyses, the coefficient of variation intra-subjects was calculated for each session. For the comparison between sessions, ANOVA for repeated measures, delta percentage, intraclass correlation coefficients, standard error of measurement, and minimal difference were used. Results: The results demonstrated that tests with less complexity, such as the vertical jump, do not require previous familiarization sessions. In contrast, tests composed of a greater number of motor actions, such as acceleration, deceleration, and change of direction, like the agility T-test, require at least three familiarization sessions before testing. Furthermore, when maximal effort anaerobic power is tested, such as the repeated running sprint test, motivation must be considered. Conclusion: The familiarization process is important to determine the performance of young soccer players, especially performance activities with more complex tasks that demand greater motor organization